Imagens errantes: a comunicação nos têxteis do mercado global - Garcia, Maria Carolina (2010)
The 15th and 16th centuries Great Navigations introduced new consumer habits in Europe and the Americas, for the expansion of intercontinental commercial routes allowed the entrance of rare products in these markets. Among those, there were cotton textiles adorned with flower patterns, known as chintzes, which in this study are referred to under communication optics. Considered as typical goods from certain regions, they were very much appreciated and acquired by travellers in order to manufacture clothes, multiplying their presence in various countries and allowing a large dislocation of foreign images. If commerce and use suggest the possibility of reaching cultural significations previously considered inaccessible, or even the chance of creating a bond with a distant Other, floral cottons from these countries supposedly would keep, inside image layers, a certain symbolic heritage. This research aims to decipher in which way and to which extent these souvenir-images of chintzes establish communicational bonds with consumers from various cultures, allowing images to have a post-life. In order to do so, it uses the concepts of primary and secondary media from Harry Pross Media Theory, the studies on communicational bonding and iconophagy by Norval Baitello Júnior and the postulations on Image Theory spread by Hans Belting and Aby Warburg. In the scope of textiles, an apparent evolution incentives consumption, or devouration, of one image by the other, characterizing iconophagy processes. Therefore, this study accompanies the chintzes journey in the international market, aiming to detect the presence of moving images and also to understand the symbolic migration in floral printings. The reflection focuses specially in Mexico, going from images present in textiles produced by zapotec natives, commonly chosen by painter Frida Kahlo to organize her looks. The analysis considers to which extent they mingle with other culture images, resisting and surviving, no matter if the interchange of knowledge and artisan techniques among peoples comes to produce adaptations for industrial purposes. While addressing the presence of erratic and mongrel images in the artist s wardrobe, the study investigates in which ways the public image of Frida Kahlo works as a bridge to reach significations dislocated in the moving market of souvenirs, which, in turn, would refresh itself with simulacrums of the aimed bonds. As a result, the research concludes that the textile can be considered a secondary media which adds to the body so as to expand its presence in the world in order to win the battle against death, establishing communicational bonds among cultures and favoring the post-life of the images